Electrochemical Impedance and its Applications in Energy‐Storage Systems. Issue 8 (11th June 2018) - Qu, Deyang; Wang, Gongwei; Kafle, Janak; Harris, Joshua; Crain, Logan; Jin, Zhihong; Zheng, Dong
Abstract: Electrochemical impedance is a powerful tool in the investigation of electrochemical systems. It obtains kinetic information of an interfacial process in the vicinity of a stable state by applying a low‐amplitude sinusoidal potential‐modulation signal on the stable (may not be completely at equilibrium) potential, and from the responding current signal, the kinetic information can be obtained. Here, the fundamental impedance responses of the common electrochemical processes, e.g., double‐layer, charge transfer, and diffusion are introduced with respect to energy‐storage systems. The impedance response of porous electrodes and the transmission‐line model are emphasized. Numerical fitting and simulation through an equivalent circuit are reviewed with the examples of the electrodes used in batteries, supercapacitors, and fuel cells. Abstract : The fundamental theories and applications of electrochemical impedance in energy storage are reviewed. Electrochemical impedance bridges the steady‐state and the transient state, which limits deviation from the steady state and avoids the irreversible modification of a battery system under study. The aim is to introduce this powerful tool of electrochemical analysis for research in the energy area.